Molecular effects of photon irradiation and subsequent aftercare treatment with dexpanthenol‐containing ointment or liquid in 3D models of human skin and non‐keratinized oral mucosa. Issue 5 (5th January 2021) - Huth, Sebastian; Marquardt, Yvonne; Huth, Laura; Schmitt, Laurenz; Prescher, Kirsten; Winterhalder, Philipp; Steiner, Timm; Hölzle, Frank; Eble, Michael; Malte Baron, Jens
Abstract: This study aimed to investigate the molecular effects of radiation and subsequent aftercare treatment with dexpanthenol‐containing ointment and liquid on established full‐thickness 3D skin models depicting acute radiodermatitis and mucositis. To mimic radiomucositis and radiodermatitis, non‐keratinized mucous membrane and normal human skin models were irradiated with 5 Gray. Afterwards, models were treated topically every second day with dexpanthenol‐containing ointment or liquid in comparison with placebo and untreated controls. On day 7 after irradiation, histological examination showed impairments in irradiated models. In contrast, models treated with dexpanthenol‐containing ointment or liquid showed a completely restored epidermal part. While gene expression profiling revealed an induction of genes related to a pro‐inflammatory milieu, oxidative stress and an impaired epidermal differentiation after irradiation of the models, aftercare treatment with dexpanthenol‐containing ointment or liquid revealed anti‐oxidative and anti‐inflammatory effects and had a positive effect on epidermal differentiation and structures important for physical and antimicrobial barrier function. Our findings confirm the potential of our established models as in vitro tools for the replacement of pharmacological in vivo studies regarding radiation‐induced skin injuries and give indications of the positive effects of dexpanthenol‐containing externals after radiation treatments as part of supportive tumor treatment.